Prevalence and causes of congenital microcephaly in the absence of a Zika virus outbreak in southern Brazil - Silvani Herber; André A. Silva; Maria Teresa V. Sanseverino; Luciana Friedrich; Tani M.S. Ranieri; Catia Favreto; Lucas R. Fraga; Anna P. Terra; Ida V.D. Schwartz; Lavínia Schuler-Faccini (Elsevier, 2019)
Objective: The aim of this study was to identify the causes of congenital microcephaly in Rio Grande do Sul, a state in southern Brazil, where no ZIKV outbreak was detected, from December 2015 to December 2016, which was the period when ZIKV infection was at its peak in northeast Brazil. Methods: This was a cross-sectional study where all notifications of congenital microcephaly in the state of Rio Grande do Sul were included for analysis. Evaluation of cases followed the guidelines of the Brazilian Ministry of Health. Dysmorphological and neurological evaluations were performed by a specialized team, and genetic tests and neuroimaging were performed when clinically indicated. STORCH infections were diagnosed using standard tests. ZIKV infection was diagnosed through maternal serum RT-PCR and/or neuroimaging associated with clinical/epidemiological criteria. Results: From 153 744 registered live births in the study period, 148 cases were notified, but 90 (60.8%) of those were later excluded as "non-confirmed" microcephaly. In the 58 confirmed cases of microcephaly (prevalence = 3.8/10 000 live births), congenital infections (syphilis, toxoplasmosis, cytomegalovirus, and ZIKV) constituted the predominant etiology (50.0%), followed by isolated CNS (15.5%), and genetic syndromes (10.3%). Congenital ZIKV syndrome (CZS) with typical phenotype was diagnosed in three cases (5.2% of all confirmed microcephaly cases or 10.4% of all congenital infections). Conclusion: In Rio Grande do Sul, where no outbreak of ZIKV infection was recorded, congenital infections were the leading cause of congenital microcephaly, and the attributable risk for CZS in the etiology of microcephaly was 5.2%. Resumo: Objetivo: Identificar as causas da microcefalia congênita no Rio Grande do Sul, Região Sul do Brasil, onde não foi detectado surto de ZIKV, de dezembro de 2015 a dezembro de 2016. Esse foi o período em que a infecção por ZIKV estava em seu auge no Nordeste do Brasil. Métodos: Este é um estudo transversal no qual todas as notificações de microcefalia congênita no estado do Rio Grande do Sul foram incluídas para análise. A avaliação dos casos seguiu as orientações do Ministério da Saúde. A avaliação dismorfológica e neurológica foi feita por uma equipe especializada e os testes genéticos e as neuroimagens foram feitos quando indicado clinicamente. As infecções STORCH (Sífilis, Toxoplasmose, Rubéola, Citomegalovírus e Herpes simples) foram diagnosticadas utilizando testes padrão. A infecção por ZIKV foi diagnosticada por meio da transcriptase reversa seguida de reação em cadeia da polimerase (RT-PCR) no soro materno e/ou neuroimagem associada a critérios clínicos/epidemiológicos. Resultados: De 153.744 nascidos vivos registrados no período do estudo, 148 bebês foram casos notificados, porém 90 (60,8%) casos foram excluídos posteriormente como microcefalia "não confirmada". Nos 58 casos confirmados de microcefalia (prevalência = 3,8/10.000 nascidos vivos), as infecções congênitas (sífilis, toxoplasmose, citomegalovírus e ZIKV) constituíram a etiologia predominante (50,0%), seguidas de doenças ligadas ao SNC isolado (15,5%) e síndromes genéticas (10,3%). A síndrome congênita do ZIKV (SCZ) com fenótipo típico foi diagnosticada em três casos (5,2% de todos os casos confirmados de microcefalia ou 10,4% de todas as infecções congênitas). Conclusão: No Rio Grande do Sul, Brasil, onde não foi registrado surto de infecção por ZIKV, a principal causa de microcefalia congênita foram infecções congênitas e o risco atribuível para SCZ na etiologia de microcefalia foi de 5,2%. Keywords: Microcephaly, ZIKV, Congenital infection, Palavras-Chave: Microcefalia, ZIKV, Infecção congênita